To Whom Belongs the Land?: Leviticus 25 in an African liberationist reading - Mtshiselwa, Ndikho (Bible and theology in Africa, 2018)
Introduction -- A critique of socio-economic injustice and land ownership in South Africa -- Land and socio-economic policy : analysis of the Israelite jubilee legislation in Leviticus 25:8-55 -- An African liberationist reading of Leviticus 25:8-55 -- Conclusion of the study